Encountering Place: Investigating the Materiality of Place Through Printmaking Practice - Lukowska, Monika Maria (Curtin University, 2018)
Through creative practice and an exegesis, this research seeks to understand the ways in which the materiality of place can inform art practice. I compare the experience of place in my hometown, Katowice, Poland, to my current home in Perth, Australia. The creative research encompasses a series of artworks through which I explore printmaking methods that can elucidate my experience of place while providing an insight into the relationship between place, materiality, and art practice.